Rehabilitation for Marfan Syndrome - Hartanto, Christi E.; Rondonuwu, Gloria E .; Gessal, Joudy (Universitas Sam Ratulangi, 2024)
Abstract: Marfan syndrome is a spectrum of disorders caused by a heritable genetic defect of connective tissue that has an autosomal dominant mode of transmission. The defect itself has been isolated to the FBN1 gene on chromosome 15, which codes for the connective tissue protein fibrillin. Abnormalities in this protein cause a myriad of distinct clinical problems, of which the musculoskeletal, cardiac, and ocular system problems predominate. The skeleton of patients with Marfan syndrome typically displays multiple deformities. Mitral valve prolapses that requires valve replacement can occur as well. Given the variable expressivity of Marfan Syndrome, no single sign is pathognomonic; the diagnosis is made on clinical grounds on the basis of typical abnormalities. We reported a boy, 12 years old, referred from surgeon with diagnosis pectus carinatum pro brace. Chest protusion appeared since age 6, getting bigger without any complaint but cosmetic. Other complaints on feet which looked flat, sometimes ankle sore after long distance running or futsal. He was the first child and no family history had a condition like him. His hobby was playing futsal, and daily activities were independent without assistive devices. General appearance and vital signs were normal, cardiorespiratory assessment was normal, BMI on percentile 10-25, arm span to height ratio 1.09, lens subluxation of left eye, lens dislocation of right eye, poor standing balance, inadequate toe off, thoracic hyperkyphotic, positive wrist sign, true leg length discrepancy of 1 cm (left>right), bilateral ankle ROM limitation, rigid flat feet suspected bilateral vertical talus, left hallux valgus, Marfan syndrome score 9, and normal echocardiography. In this patient, we gave semi rigid thoraco-lumbo-sacral orthosis (TLSO) with 3 points pressure system and rigid bar on protution area (custom molded). resistance exercise (F: 3x/week, I: moderate fatigue, Borg scale 13-15/20, T: 8-15 reps/ set, 2-3 set/ session, T: major muscle group upper and lower extremities aerobic exercise (F: 3x/week, I: moderate to vigorous, borg scale 13-15/20, T: ≥60 min/session, @5-10 min warming up and cooling down (stretching), T: sport (swimming, running, cycling). The patient was referred to a surgeon for a brace. In conclusion, this case report highlights the multidisciplinary management of patients with Marfan syndrome. Keywords: Marfan syndrome; typical abnormalities; multiple deformities